2012
DOI: 10.1504/ijetm.2012.049240
|View full text |Cite
|
Sign up to set email alerts
|

Microbial characterisation of vermicompost and compost of urban waste processed by three earthworm species - Eudrilus eugeniae, Eisenia fetida and Perionyx excavatus

Abstract: Species diversity of bacteria, fungi and actinomyctes of vermicompost and compost of the organic fraction of municipal solid waste, vegetable market waste and flower waste were assessed using pour plate technique. Of the total 91 entities, 62 were bacteria and 29 were actinomycetes in MW, followed by that of MSW and FW, with 59 and 55 bacterial; 25 and 22 actinomycetes entities, respectively. The biodiversity of bacteria and actinomycetes were significantly higher in the vermicomposts produced by Eudrilus euge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In soil-borne plant disease control via soil amendment with vermicompost, antagonistic microbes provided direct suppression in the mycelial growth of fungal pathogens [ 19 , 22 ], relying on interference competition for resources between plant pathogens and antagonistic microbes in vermicompost [ 36 ]. Antagonistic microbes found in AF vermicompost, such as Bacillus spp., Pseudomonas spp., and Streptomyces spp., were more diverse than those in TG vermicompost [ 37 ]. Therefore, AF vermicompost was found to exhibit better suppressive ability than TG vermicompost, as presented in this study ( Figure 1 , Figure 2 and Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In soil-borne plant disease control via soil amendment with vermicompost, antagonistic microbes provided direct suppression in the mycelial growth of fungal pathogens [ 19 , 22 ], relying on interference competition for resources between plant pathogens and antagonistic microbes in vermicompost [ 36 ]. Antagonistic microbes found in AF vermicompost, such as Bacillus spp., Pseudomonas spp., and Streptomyces spp., were more diverse than those in TG vermicompost [ 37 ]. Therefore, AF vermicompost was found to exhibit better suppressive ability than TG vermicompost, as presented in this study ( Figure 1 , Figure 2 and Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…It implied that amending AF vermicompost to the soil might facilitate the exploitative competition of beneficial microbes in comparison to TG vermicompost. In addition to nutrient content, Pattnaik and Reddy [ 37 ] revealed that AF vermicompost had significantly more species diversity in microbes and biomass, especially actinomycetes, than TG vermicompost. Applying AF vermicompost rather than TG vermicompost via soil amendment might introduce a higher number of beneficial microbes.…”
Section: Resultsmentioning
confidence: 99%
“…This process was correlated to the sufficient of nutrients that was easily absorbed and used by plant particularly in leaves formation [13]. Pattnaik and Reddy [14] stated that the vermicompost application increased the number of leaves due to the nutrient content in vermicompost such as N, P, K and Mg.…”
Section: Number Of Leavesmentioning
confidence: 99%
“…Essential nutrient content and hormone in vermicompost could accelerate leaves formation rate. N in vermicompost was used optimally by plant so that photosynthesis process in leaves increased [14]. The photosynthesis result then was distributed to all parts of plant and it affected the length and width of leaves of plant [24].…”
Section: Length and Width Of Leaves (Cm)mentioning
confidence: 99%
See 1 more Smart Citation